The Relationship between Knowledge of Reproductive System with Reproductive Health Care Attitudes in Senior High School Student in Indonesia - Fauziani Aulia Luthfiana Nalwin; Milla Listiawati; Epa Paujiah (CV. Generasi Intelektual Digital (GEN ID), 2024)
Reproductive health is a primary concern among teenagers in Indonesia, especially those in high school. There are numerous cases of risky sexual behaviour are found in high schools. It occurs among them because of several factors, one of which is the lack ofknowledge, which leads them to have a poor attitude towards their reproductive health. This study aims to determine the relationship between high school students' knowledge about the reproductive system and their reproductive health care attitudes. This studyutilizes a quantitative approach and employs a correlational study. The sample are taken from a group of 35 students from class XI MIPA 1, that had not studied the reproductive system materials, and another 35 students from class XI MIPA 7, that had studied it, which is determined using the purposive sampling technique. The results of knowledge test for the reproductive system in XI MIPA 1 showed an average score of 51,29, while XI MIPA 7 scored an average of 81,71. Meanwhile, the results of the reproductive health care attitudesurvey for XI MIPA 1 showed an average score of 44,40, and for XI MIPA 7, it was 55. Based on the correlation test, XI MIPA 1 had a correlation coefficient of 0,677 with a significance score of 0,000 (< 0,05). In Class XI MIPA 7, the correlation coefficient was 0,643 with a significance score of 0,000 (< 0,05). As a result, this study shows that there is a strong positive relationship between students' knowledge about the reproductive system and their reproductive health care attitudes.